Combining chemical and lead isotope analyses with 3-D geometric–morphometric shape analysis: A methodological case study of socketed bronze arrowheads from the southern Levant. (June 2020) - Yahalom-Mack, Naama; Herzlinger, Gadi; Bogdanovsky, Alexander; Tirosh, Ofir; Garfinkel, Yosef; Dugaw, Sean; Lipschits, Oded; Erel, Yigal
Abstract: In this study, the shape of socketed bronze arrowheads is analysed and expressed as a series of mathematical trends which are then compared to chemical and lead isotope composition, as well as to the categorization of traditional non-computerized typology. It is shown that while traditional typology has statistical validation, additional important information can be gleaned from 3-D geometric morphometric shape analysis (3DGM), particularly when combined with material analyses. For example, arrowheads that are traditionally categorized as a single type demonstrate minute shape differences that correlate with the sites where they were found. This micro-variability, detected only through 3DGM, has potential cultural, chronological and regional implications. Most importantly, this pilot study shows that chemical and isotopic composition is correlated to a specific shape trend, revealed through computerized analysis, rather than to the traditional typological classification. This opens up new vistas for a more advanced analysis of archaeological finds.